Bounds on the effective transport coefficients of two-phase media from discrete theoretical and experimental data - Tokarzewski, Stanisław; Gałka, Andrzej; Andrianov, Igor (Computer Assisted Methods in Engineering and Science, 2023)
By applying Pade approximants and continued fractions technique developed in [1, 2, 3, 24] we investigate a composite material of the effective modulus e(h) consisting of two components of real moduli 1 and 2, respectively, where h= 2/ 1. By starting from K power expansions of e(h) at fixed points h= h1, h2 , ... ,hK the infinite set of the general inequalities specifying explicitly the upper and lower bounds on e(h)/ 1 are derived. Our estimations generalize the previous bounds reported in [13, 17, 22] . The inequalities achieved are applied for the evaluation of the upper and lower bounds on e(h)/ 1 from the given experimental measurements.